Quantum Chemical Calculations (QSAR) of Antipyrine Drug and Its Metabolites - A. Ibrahim, Ammar; A. Abdalrazaq, Eid; A. Ibrahim, Maher; Yahya, Rosiyah; A. Sulliman, Entesar (Asian Journal of Chemistry, 2011)
The electronic properties of antipyrine and its metabolites have been investigated theoretically by the different methods of semi-empirical (AM1, MNDO/3 and PM3) and ab initio at STO-3G level calculations. These metabolites are of much interest due to their biological and medical importance. The charges, HOMO, LUMO, hardness (h), electronic chemical potential (μ) and global electrophilicity index (w) were determined. The metabolites of A4 (according to MNDO/ 3) and A6 (according to AM1, PM3 and ab initio) have relatively low LUMO-HOMO differences indicating that these compounds would be the most reactive metabolites.